Piptoporellus taiwanensis sp. nov. (Polyporales, Fomitopsidaceae) from Taiwan and its phytochemistry - Jen, Chia-I; Lai, Ming-Nan; Ariyawansa, Hiran A.; Bandara, Asanka R.; Ng, Lean-Teik (Phytotaxa, 2023)
Piptoporellus is a recently proposed genus placed under Fomitopsis-like taxa in the Antrodia clade. Four species of Piptoporellus are known, of which three are distributed in China, and one in Africa. A specimen collected around Sun Moon Lake, Nantou County, Taiwan proved to be the first documentation of Piptoporellus in Taiwan. Based on morpho-molecular data, a new species, Piptoporellus taiwanensis, is introduced. In a multi-gene. phylogeny of nuclear ribosomal internal transcribed spacer (nrITS) region, large subunit RNA gene (nrLSU), small subunit RNA gene (nrSSU), and translation elongation factor 1-α gene (tef1-α), the novel taxon formed a distinct clade sister to P. hainanensis and P. triqueter. Phenotypically our strain differs from other Piptoporellus species in having yellow to orange pileus, buff to yellow pore surface, thin-walled basidiospores, and a dimitic hyphal system. Chemical analysis showed that this novel species contained about 3.878 g of total polysaccharides, 112.9 mg of total phenols, 182.9 mg of total flavonoids, 34.33 mg of total triterpenoids, and trace amounts of alkaloids per 100 g of dried fruiting bodies. This study has shed light on the diversity of Piptoporellus taxa in Taiwan and has also shown that this novel species contains significant amounts of polysaccharides, polyphenols, and triterpenoids.